Benefits of the fixed‐ratio combination of insulin glargine 100 units/mL and lixisenatide (iGlarLixi) in Japanese people with type 2 diabetes: A subgroup and time‐to‐control analysis of the LixiLan JP phase 3 trials. (16th September 2020) - Terauchi, Yasuo; Yabe, Daisuke; Kaneto, Hideaki; Amano, Atsushi; Baxter, Mike; Watanabe, Daisuke; Watada, Hirotaka; Inagaki, Nobuya
Abstract: Aims: To explore the impact of baseline characteristics on clinical outcomes in the phase 3 LixiLan JP trials which evaluated the efficacy and safety of iGlarLixi, a titratable fixed‐ratio combination of insulin glargine 100 units/mL (iGlar) and GLP‐1 RA lixisenatide (Lixi), vs Lixi (JP‐O1, NCT02749890) or iGlar (LixiLan JP‐O2, NCT02752828; JP‐L, NCT02752412) in Japanese people with type 2 diabetes uncontrolled on oral antidiabetes drugs (OADs; JP‐O1, JP‐O2) or OADs and basal insulin (JP‐L). Materials and methods: Glycated haemoglobin (HbA1c) change from baseline to week 26 was assessed within patient subgroups. Subgroups were defined by dipeptidyl peptidase‐4 inhibitor use at screening (JP‐O1, JP‐O2 only), baseline HbA1c (<8%, ≥8%), baseline BMI (<25, ≥25 kg/m 2 ) and age (<65, ≥65 years). Incidences of hypoglycaemia (baseline HbA1c, BMI and age subgroups) and gastrointestinal disorders (age subgroup) were evaluated over 52 (JP‐O1) or 26 weeks (JP‐O2, JP‐L). Time to control (first HbA1c <7% or fasting plasma glucose [FPG] ≤130 mg/dL; JP‐O2 only) was also assessed. Results: HbA1c reductions were consistently greater with iGlarLixi vs iGlar or Lixi across all subgroups, and iGlarLixi was equally effective in all subgroups. Incidences of documented symptomatic hypoglycaemia (plasma glucose ≤3.9 mmol/L) were higher with iGlarLixi vs Lixi and generally comparable with iGlar. Across age subgroups, incidences of gastrointestinal disorders with iGlarLixi were higher vs iGlar, but lower vs Lixi. Median time to HbA1c or FPG control was shorter with iGlarLixi vs iGlar. Conclusions: iGlarLixi was consistently effective across all baseline characteristic subgroups, with more patients achieving glycaemic control vs iGlar early in treatment.